2017
DOI: 10.2139/ssrn.3173579
|View full text |Cite
|
Sign up to set email alerts
|

Bias, Bullshit and Lies: Audience Perspectives on Low Trust in the Media

Abstract: The news media does a good job in helping separate fact from fic:on Social media does a good job in helping separate fact from fic:on Why? Journalis:c process Good storytelling/depth Trusted brands Why? Bias Exaggera:on/ sensa:onalism Low standards Why? Broad range of sources/views Authen:city Why? Low quality/unreliable No checks Agenda driven/ opinionated 35% 41% 40% 35% 25% 24% Q6_2017_1/2. Please indicate your level of agreement with the following statements-The news media/social media does a good job in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 7 publications
1
53
0
7
Order By: Relevance
“…Desde el punto de vista de la credibilidad, los espectadores españoles confían más en las cadenas de televisión antes que en cualquier otro medio (Newman y Fletcher, 2017). No obstante, las cadenas de televisión también son criticadas por anteponer "la rapidez a la precisión, por favorecer la opinión sobre los hechos y por impulsar agendas partidistas" (Newman y Fletcher, 2017, p.5) o por su sensacionalismo y falta de objetividad (HMG, 2020), Por su parte, en prensa escrita, las fotografías fijan y destacan acontecimientos y detalles de una realidad concreta, lo que redunda en un incremento de la credibilidad y en una fuente de información fidedigna, lo que, a su vez, favorece su recuerdo y aumenta su efecto persuasivo a largo plazo (Torres, 2006;Fernández, 2013).…”
Section: La Televisión Y La Prensa Como Fuentes Informativas Durante La Crisis Sanitariaunclassified
“…Desde el punto de vista de la credibilidad, los espectadores españoles confían más en las cadenas de televisión antes que en cualquier otro medio (Newman y Fletcher, 2017). No obstante, las cadenas de televisión también son criticadas por anteponer "la rapidez a la precisión, por favorecer la opinión sobre los hechos y por impulsar agendas partidistas" (Newman y Fletcher, 2017, p.5) o por su sensacionalismo y falta de objetividad (HMG, 2020), Por su parte, en prensa escrita, las fotografías fijan y destacan acontecimientos y detalles de una realidad concreta, lo que redunda en un incremento de la credibilidad y en una fuente de información fidedigna, lo que, a su vez, favorece su recuerdo y aumenta su efecto persuasivo a largo plazo (Torres, 2006;Fernández, 2013).…”
Section: La Televisión Y La Prensa Como Fuentes Informativas Durante La Crisis Sanitariaunclassified
“…Consumer trust in the quality, accuracy and coverage of news reports by intermediaries is essential in that relationship. Newman & Fletcher (2017) carried out an in-depth survey and analysis of consumer perceptions of the quality of news in nine countries. They find that people do not operate with categorical distinctions between "fake" and "real" news but rather see the difference as one of degree.…”
Section: Some Evidence On Consumer Trust and The Quality Of Newsmentioning
confidence: 99%
“…The Gallup data also confirm that distrust is higher among the political right (Republicans) than the left (Democrats). Newman & Fletcher (2017) found that two-thirds of the respondents were concerned about bias, spin, and hidden agendas in news media. Their survey shows how news media polarization varies across countries.…”
Section: Some Evidence On Consumer Trust and The Quality Of Newsmentioning
confidence: 99%
“…Das Gegenkonzept des "public engagement" setzt auf eine stärkere Publikumsbeteiligung: "Die umfassende Demokratisierung der ‚postindustriellen' Gesellschaften tritt […] in Konflikt zur Wahrheitsorientierung der Wissenschaft, indem sie die Distanz der Wissenschaft durch Partizipations-und Integrationsforderungen zu verringern oder gar zu beseitigen sucht." (Weingart, 2001: 354) Im Publikum wachsen die Ablehnung epistemischer Autoritäten und die Neigung zu divergenten Sichtweisen, wie sich in Bevölkerungsbefragungen zur Wissenschaft (Funk & Rainie, 2015;Wissenschaft im Dialog, 2017: 11-24, 27-28) und zum Journalismus (Newman & Fletcher, 2017;Ziegele et al, 2018) zeigt. Allerdings lässt sich ein massiver Vertrauensentzug zumindest in Deutschland für die Wissenschaft (z.…”
unclassified